On the role of minority carriers in the frequency dependence of organic magnetoresistance - Janssen, Paul; Wagemans, Wiebe; Verhoeven, W.; van der Heijden, E. H. M.; Kemerink, Martijn; Koopmans, Bert (Synthetic metals, 2011)
In this work we investigate the frequency dependence of organic magnetoresistance (OMAR) both in small molecule-based (Alq3) and polymer (PPV derivative) materials, and investigate its thickness dependence. For all devices, we observed a strong decrease in magnetoconductance (MC) with increasing frequency of the ac component of the applied magnetic field. Moreover, we observed a strong reduction of the cut-off frequencies for increasing film thickness. By means of admittance spectroscopy and device simulations, we show that the cut-off frequency is related to the inverse transit time of the minority charge carriers. These observations confirm the important role of minority carriers in OMAR, and show that changes in OMAR are not only due to microscopic mechanisms, but also device physics is of significant relevance.